Effect of combined drink cans and steel fibers on the impact resistance and mechanical properties of concrete - Syamsir A.; Mubin S.M.; Nor N.M.; Anggraini V.; Nagappan S.; Sofan A.M.; Muda Z.C. (Universiti Malaysia Pahang, 2023)
This study investigated the combine effect of 0.2 % drink cans and steel fibers with volume fractions of 0%, 0.5%, 1%, 1.5%, 2%, 2.5% and 3% to the mechanical properties and impact resistance of concrete. Hooked-end steel fiber with 30 mm and 0.75 mm length and diameter, respectively was selected for this study. The drinks cans fiber were twisted manually in order to increase friction between fiber and concrete. The results of the experiment showed that the combination of steel fibers and drink cans fibers improved the strength performance of concrete, especially the compressive strength, flexural strength and indirect tensile strength. The results of the experiment showed that the combination of steel fibers and drink cans fibers improved the compressive strength, flexural strength and indirect tensile strength by 2.3, 7, and 2 times as compare to batch 1, respectively. Moreover, the impact resistance of fiber reinforced concrete has increase by 7 times as compared to non-fiber concretes. Moreover, the impact resistance of fiber reinforced concrete consistently gave better results as compared to non-fiber concretes. The fiber reinforced concrete turned more ductile as the dosage of fibers was increased and ductility started to decrease slightly after optimum fiber dosage was reached. It was found that concrete with combination of 2% steel and 0.2% drink cans fibers showed the highest compressive, split tensile, flexural as well as impact strength. The Authors 2020.